Assimilation, Resistance, Rapprochement, and Loss: Response to Woodrum, Faircloth, Greenwood, and Kelly - Michael Corbett (Journal of Research in Rural Education, 2009)
To begin I would like to thank Michael Barbour for suggesting this themed issue in the Journal of Research in Rural Education. I would also like to thank Kai Schafft for taking up this suggestion and recruiting such an outstanding group of scholars concerned with rural education broadly defined. These scholars suggest in similar yet different ways that we need to think more broadly about what rural means and indeed how the connections between people and place matter. As each commentator seems to agree, all manner of these connections are currently under threat. In addition to the established historical stories of dispossession so well articulated by each author, contemporary economic upheavals have destabilized the connection between people and place secured by stable financial systems and real estate markets. Little seems certain these days and rural North America feels the heat disproportionately, as usual.